Anatomy of a fiscal shock: Deconstructing the pandemic’s impact on Indonesia’s local tax revenue - Muamarah, Hanik Susilawati; Marsono (Badan Pemeriksa Keuangan Republik Indonesia, 2026)
The COVID-19 pandemic disrupted local economic activity and exposed vulnerabilities in subnational public finance. However, limited empirical evidence explains how the structure of the local tax base influences fiscal resilience to mobility shocks in developing countries. Drawing on tax handle theory, this study examines the impact of the COVID-19 pandemic on local tax revenue in Indonesia, focusing on heterogeneity across tax types and the moderating role of pre-pandemic fiscal vulnerability, defined as dependence on mobility-based taxes. Using a fixed-effects model on panel data covering 3,136 observations from 448 regencies and municipalities over 2017–2023, the results show that the aggregate decline in local tax revenue was primarily driven by contractions in mobility-sensitive taxes, particularly restaurant and entertainment taxes. This relationship is confirmed by the main moderation results, which show that regions with high pre-pandemic fiscal vulnerability exhibit a significantly stronger negative relationship. Although weakened, the effect persisted into the recovery period (2022–2023). This study provides empirical evidence that the local tax base structure determines fiscal resilience to mobility shocks more than the general level of fiscal autonomy, highlighting the need for local governments to diversify their revenue sources toward those that are relatively more resilient to external shocks.